The exemplary role of farmer institutional administrators as a strengthener for the holistic and integrative reform of the agricultural development paradigm - Hadi, Syamsul; Aprisco, Handa; Abdillah, Muhammad Faris; Suroso, Bejo (Holistic: Journal of Tropical Agriculture Sciences, 2025)
Background: The agricultural development paradigm, which has shifted evolutionary from traditional agriculture to the current sustainable agriculture stage, has not been able to create prosperity for both farmers and the environment. Since the establishment of this sustainable agriculture paradigm, the back-to-nature movement has not changed the fate of farmers and the environment. This condition indicates that the three pillars/dimensions of sustainable agricultural development have not been successful in economic, sociological, and ecological dimensions, because one of the causes is the role of farmer institutions is not optimal, including not being a role model for its members. The purpose of this study is to strengthen the impact of the implementation of a holistic and integrative agricultural development paradigm through the exemplary role of farmer institutions for its members. Method: method used is descriptive through the Literature Review (SRL) technique approach using several published and unpublished research articles. Some theories used are the history of the evolution of agricultural paradigms in Indonesia starting from the traditional stage, agricultural intensification, agricultural diversification and industrialization, sustainable and inclusive agriculture to the optional holistic and integrative paradigm and the theory of farmer group role models. Findings: The results of this study reveal that the role model factor of farmer group administrators can have implications for the level of farmer participation in following all recommendations. In line with the exemplary role model of farmer group administrators, this evolutionary paradigm shift in agricultural development toward a holistic and integrative one will positively impact the acceleration of improving the welfare of farming communities and their environment. Conclusion: The conclusion of this study is that the paradigm shift in agricultural development in Indonesia from before the 20th century to the 21st century (sustainable and inclusive agricultural development), including holistic and integrative options, has not been able to alleviate poverty in agriculture. Novelty/Originality of this article: A holistic and integrative sustainable agricultural development paradigm will have a very positive and accelerating impact on poverty alleviation in the agricultural sector if it strengthens the role of exemplary farmer institutions.